Jewish Interconnectivity and Diasporic Unrest under Trajan: Stereotypes and Uneasy Histories - Bonar, Chance E. (Journal of ancient Judaism, 2025)
The Jewish revolts in the eastern Mediterranean diaspora between 116-117 CE offer a fruitful opportunity to explore how realities and perceptions of "Jewish interconnectivity" affect ancient and modern historical narration. This article explores how Eusebius, Cassius Dio, and others explain simultaneous Jewish unrest in North Africa and Mesopotamia, as well as why Judaea suffered sociopolitical and military consequences of actions that are attributed to diasporic Jews.